PEMBELAJARAN RANAH AFEKTIF ANTARA HARAPAN DAN KENYATAAN - Pulungan, Muhammad Yusup (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2013)
Today many parties are demanding an increasing in the intensity and quality of implementation of affective education in formal educational institutions. This situation has stirred the collective consciousness of the need to reinvigorate our nation's morality dimension. It could be argued, the moral crisis that hit the nation became increasingly marked by rampant sexual acts, violence, murder,  gambling, pornography, rising juvenile delinquency cases, the number of drug addicts and drinking and other social diseases spreading more chronic. According to the social observer, a moral crisis as it is partly the fault of national educational institutions has not considered optimal in shaping the personality of students. It so happens because the valuation models that apply to some subjects related to education during this value only measures cognitive ability learners.   One attempt was made  expectations ahead to rebuild the lost character of the nation is the rise of integrated education patterns applied to the school system. Patterns of integration are not only transferring knowledge to students, but the coaching attitude  emphasis on education also  influences the affective domain of teaching and learning activities in the system. There are still a lot of flaws and things  -  other things that have to be met and continue to be improved in the system development of the affective domain in education. Thus this paper is born with an explanation of how the ideal application of the affective domain in education was implemented as much as possible either at school, in the family or in the neighbourhood as a whole is indispensable in order to regrow the lost character of the nation.